Sentidos e significados de professores de matemática ao usarem resolução de problemas para abordar conteúdos geométricos no ensino médio - Alves, Larissa Evelyn Santos Silva (2021)
This study presents a qualitative approach, whose main objective was to analyze the senses and meanings of mathematics teachers when addressing geometric contents in high school classes, through Problem Solving. The teachers participating in the research were volunteers who work with high school classes from two Centers of Excellence of the state public network, in the city of Aracaju-SE. To this end, emphasis was placed on two central questions: How do high school math teachers approach geometric content? What senses and meanings do they attribute to these contents, using Problem Solving? In seeking to answer these questions, the theory of the Relation with Knowledge was taken as the basis for data analysis under the assumptions of Charlot and understanding of Problem Solving, from Onuchic and other authors. The specific objectives were: to identify whether or not there were gaps in the geometric formation process of these participating teachers, whether this phenomenon interferes in the understanding and the way they plan their classes to teach geometric content; and see how these teachers appropriated the geometric contents to teach, to justify the choice of activities addressed by them when teaching these contents. As for the methodological procedures, the study had an exploratory character, being bibliographic and field research. Taking into account the period of social leave due to the COVID-19 pandemic, which has lasted until the present day, the data collection in this study took place online, with the application of a questionnaire and semistructured interview. The results reveal that the participating teachers had their basic and initial training in public school and, even for those who studied geometric content in basic school, they cannot show a relationship about what they learned from what they teach in geometry today in high school. Another aspect refers to the relationship they make about Problem Solving in their classes or how they plan, does not match what the research points out as a teaching methodology, as well as, what is recommended in the current curriculum guidelines for high school.